How Digital Transformation Drives Performance in Small and Medium Enterprises: Evidence from Emerging Markets - Josef Okemba (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has become a critical strategic capability for small and medium enterprises (SMEs) operating in emerging markets characterized by uncertainty and intense competition. This study examines how digital transformation drives firm performance by incorporating the mediating roles of innovation capability, digital marketing, knowledge management, and organizational resilience. A quantitative research design was employed using primary data collected from SME owners and senior managers through a structured questionnaire. The data were analyzed using structural equation modeling to assess both direct and indirect relationships among the constructs. The findings reveal that digital transformation has a significant positive effect on firm performance and long-term competitiveness, with innovation, marketing effectiveness, and knowledge management serving as key mediating mechanisms. Moreover, digital transformation enhances resilience and sustainability, enabling SMEs to adapt to environmental disruptions and maintain competitive positioning over time. This study contributes to the literature by providing integrated empirical evidence from emerging markets and offers practical insights for SME managers and policymakers in designing effective digital transformation strategies.